Parameterizing Generalized Laguerre Functions to Compute the Inverse Laplace Transform of Fractional Order Transfer Functions - Karsky, Vilem (Institute of Automation and Computer Science, Brno University of Technology, 2018)
This article concentrates on using generalized Laguerre functions to compute the inverse Laplace transform of fractional order transfer functions. A novel method for selecting the timescale parameter of generalized Laguerre functions in the operator space is introduced and demonstrated on two systems with fractional order transfer functions.
Keywords: Fractional order systems; generalized Laguerre functions; free parameters; inverse Laplace transform